Obesity and change in estimated GFR among older adults. - de Boer, Ian H; Katz, Ronit; Fried, Linda F; Ix, Joachim H; Luchsinger, Jose; Sarnak, Mark J; Shlipak, Michael G; Siscovick, David S; Kestenbaum, Bryan (Am J Kidney Dis, 2009)
BACKGROUND: The prevalence of chronic kidney disease is growing most rapidly among older adults; however, determinants of impaired kidney function in this population are not well understood. Obesity assessed in midlife has been associated with chronic kidney disease. STUDY DESIGN: Cohort study. SETTING & PARTICIPANTS: 4,295 participants in the community-based Cardiovascular Health Study, aged >or= 65 years. PREDICTORS: Body mass index, waist circumference, and fat mass measured using bioelectrical impedance. OUTCOME: Change in glomerular filtration rate (GFR) during 7 years of follow-up. MEASUREMENTS: Longitudinal estimates of GFR calculated using the 4-variable Modification of Diet in Renal Disease (MDRD) Study equation. RESULTS: Estimated GFR decreased by an average of 0.4 +/- 3.6 mL/min/1.73 m(2)/y, and rapid GFR loss (>3 mL/min/1.73 m(2)/y) occurred in 693 participants (16%). Baseline body mass index, waist circumference, and fat mass were each associated with increased risk of rapid GFR loss: ORs, 1.19 (95% CI, 1.09-1.30) per 5 kg/m(2), 1.25 (95% CI, 1.16-1.36) per 12 cm, and 1.14 (95% CI, 1.05-1.24) per 10 kg after adjustment for age, sex, race, and smoking. The magnitude of increased risk was larger for participants with estimated GFR < 60 mL/min/1.73 m(2) at baseline (P for interaction < 0.05). Associations were substantially attenuated by further adjustment for diabetes, hypertension, and C-reactive protein level. Obesity measurements were not associated with change in GFR estimated using serum cystatin C level. LIMITATIONS: Few participants with advanced chronic kidney disease at baseline, no direct GFR measurements. CONCLUSION: Obesity may be a modifiable risk factor for the development and progression of kidney disease in older adults.
Keywords: Aged; Aging; Body Composition; Body Mass Index; Chronic Disease; Cohort Studies; Creatinine; Cystatin C; Female; Glomerular Filtration Rate; Humans; Kidney; Kidney Diseases; Longitudinal Studies; Male; Obesity; Risk Factors